2022
DOI: 10.3390/antibiotics11060817
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl Acetate Fraction of Bixa orellana and Its Component Ellagic Acid Exert Antibacterial and Anti-Inflammatory Properties against Mycobacterium abscessus subsp. massiliense

Abstract: Mycobacterium abscessus subsp. massiliense (Mabs) causes chronic infections, which has led to the need for new antimycobacterial agents. In this study, we investigated the antimycobacterial and anti-inflammatory activities of the ethyl acetate fraction of Bixa orellana leaves (BoEA) and ellagic acid (ElAc). In silico analysis predicted that ElAc had low toxicity, was not mutagenic or carcinogenic, and had antimicrobial and anti-inflammatory activities. Apparently, ElAc can interact with COX2 and Dihydrofolate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 61 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…(Zarza-García et al, 2017). In a similar trial, the ethyl acetate extract (50 mg/kg) also reduced paw edema by 40%, being comparable to the efficiency of diclofenac (Moraes-Neto et al, 2022). Another work investigated the possible inflammatory mediators inhibited by the aqueous extract of the leaves, and the acute inflammation model was induced in Sprague-Dawley rats through the administration of carrageenan, histamine, serotonin and bradykinin in the hind legs, in addition to verifying to regression of granulomas in the model of chronic inflammation, so that in all models, the extract led to the reduction of inflammation, using doses between 50 and 150 mg/kg (Zuraini et al, 2007).…”
Section: Pharmacology Approaches Of Bixa Orellana Leavesmentioning
confidence: 78%
See 1 more Smart Citation
“…(Zarza-García et al, 2017). In a similar trial, the ethyl acetate extract (50 mg/kg) also reduced paw edema by 40%, being comparable to the efficiency of diclofenac (Moraes-Neto et al, 2022). Another work investigated the possible inflammatory mediators inhibited by the aqueous extract of the leaves, and the acute inflammation model was induced in Sprague-Dawley rats through the administration of carrageenan, histamine, serotonin and bradykinin in the hind legs, in addition to verifying to regression of granulomas in the model of chronic inflammation, so that in all models, the extract led to the reduction of inflammation, using doses between 50 and 150 mg/kg (Zuraini et al, 2007).…”
Section: Pharmacology Approaches Of Bixa Orellana Leavesmentioning
confidence: 78%
“…The ethyl acetate extract produced an antimicrobial (Minimum inhibitiory concentration (MIC) = 1.56 mg/mL) and bacteriostatic (MIC = 6.25 mg/mL) effect against Mycobacterium abscessus subsp. massiliense (Mabs) (Moraes-Neto et al, 2022). Finally, the methanolic extract presented activity against Pseudomonas aeruginosa, with maximum inhibition halo activity of 17.33 mm (Singh & Vidyasagar, 2017).…”
Section: Pharmacology Approaches Of Bixa Orellana Leavesmentioning
confidence: 99%
“…Mycobacterium abscessus (Mabs) is a cause of various types of infection including respiratory infection in patients with cystic fibrosis. EA demonstrated antimicrobial activity against Mabs due to its high binding affinity to Dihydrofolate reductase at a minimum inhibitory concentration of 1.56 mg/mL and bactericidal concentration of of 3.12 mg/mL [ 25 ].…”
Section: Reviewmentioning
confidence: 99%
“…In this way, compounds that act by affecting the functioning of DHFR can cause the death of bacteria. [52] Myricetin acts by inhibiting bacterial enzymes that are essential for bacteria. Studies involving the Escherichia coli species showed that myricetin is able to inhibit DNA gyrase, DNA helicase and RNA polymerase enzymes.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…The antimicrobial activity of ellagic acid is related to its ability to bind with Dihydrofolate reductase (DHFR), this bacterial enzyme acts in important processes related to bacterial multiplication such as nucleic acid synthesis, DNA translation, RNA transcription and replication of proteins. In this way, compounds that act by affecting the functioning of DHFR can cause the death of bacteria [52] . Myricetin acts by inhibiting bacterial enzymes that are essential for bacteria.…”
Section: Introductionmentioning
confidence: 99%